2017
DOI: 10.13044/j.sdewes.d5.0163
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Injection Timing Influence on Fuel Slip and Influence of Compression Ratio on Knock Occurrence in Conventional Dual Fuel Engine

Abstract: Compressed natural gas can be used in diesel engine with great benefits, but because of its low reactivity it is usually used in a so called dual fuel combustion process. Optimal parameters for dual fuel engines are not yet investigated thoroughly which is the motivation for this work. In this work, a numerical study performed in a cycle simulation tool (AVL Boost v2013) on the influence of different injection timings on fuel slip into exhaust and influence of compression ratio on knock phenomena in port injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The B7 in the name of fuel indicates around 7% biodiesel content, which indicates the utilization of biofuels in conventional diesel engines 52 . The injection rate timing has a direct influence on engine performance, 53 for that reason, the inlet fuel velocity is calculated from the measured injection rate, which is shown in Figure 2. Figure 2 shows the injection curve rate is shown as a nondimensional parameter, where the area under the curve presents the total injected fuel mass in one operating cycle.…”
Section: Experimental Data and Numerical Setupmentioning
confidence: 99%
“…The B7 in the name of fuel indicates around 7% biodiesel content, which indicates the utilization of biofuels in conventional diesel engines 52 . The injection rate timing has a direct influence on engine performance, 53 for that reason, the inlet fuel velocity is calculated from the measured injection rate, which is shown in Figure 2. Figure 2 shows the injection curve rate is shown as a nondimensional parameter, where the area under the curve presents the total injected fuel mass in one operating cycle.…”
Section: Experimental Data and Numerical Setupmentioning
confidence: 99%
“…Furthermore, dual fuel engines are subject to fuel slip into the exhaust port during the valve overlap period which results in an increase in HC emissions, largely composed of methane. This phenomenon occurs at all ranges of engine loads and speeds, especially in charged engines because of a positive pressure difference between intake and exhaust pipes [14].…”
Section: Conventional Dual Fuel Enginementioning
confidence: 99%
“…A detailed investigation of the multi-injection strategy was conducted in [12], where CFD analysis showed the capabilities to model the low-temperature combustion in order to achieve higher efficiency, lower nitric oxides, and lower soot emissions. In [13], the authors showed the possibilities to achieve the higher thermal efficiency of a dual fuel engine by optimising the fuel injection strategy. It is known that the fuel consumption efficiency and pollutant emissions depend on the injection system parameters, piston geometry parameters, and conditions inside the combustion chamber [14].…”
Section: Introductionmentioning
confidence: 99%